Embedding Data Analysis into the Undergraduate Actuarial Science Curriculum - Phatak, Aloke (2018)
The recent initiative by the Actuaries Institute to incorporate a data science/analytics unit at the Honours or Masters level, as well as the changes to the undergraduate curriculum that will start in 2020, means that actuarial science educators need to consider embedding data analysis and analytics throughout the undergraduate curriculum. At Curtin, we have been trialling ways of doing just that in a coherent fashion, from first-year to third-year units, so that students see data analysis as an integral part of becoming a practicing actuary. We were motivated by: